Global antiphospholipid syndrome score (GAPSS) in patients with systemic lupus erythematosus - F. A. Cheldieva; T. M. Reshetnyak; A. A. Shumilova; K. S. Nurbaeva; M. V. Cherkasova; A. M. Lila; E. L. Nasonov (Научно-практическая ревматология)
Introduction. The Global Antiphospholipid Syndrome Score (GAPSS) is a tool proposed to quantify the risk of clinical manifestations associated with antiphospholipid antibodies (aPL) and certain cardiovascular risk factors.Objective. To validate GAPSS in a cohort of patients with systemic lupus erythematosus in Russia.Material and methods. 115 patients with SLE were included in the study, including 51 (44%) patients with systemic lupus erythematosus (SLE) with antiphospholipid syndrome (APS), 14 (12%) – SLE with aPL, and 50 (44%) – SLE.Results. There was a history of thrombosis in 58 (50%) patients with 115, of them 14 (24%) had arterial thrombosis, 29 (50%) – venous, 15 (26%) – combined. Pregnancy against the background of the disease occurred in 43 women included in the study. Of them, 29 (67%) had obstetric pathology. Patients with thrombosis and obstetric pathology had a GAPSS score of 7.17±5.64, versus 4.48±4.55 without these manifestations (p=0.0003). There was a significant association between GAPSS levels and thrombosis – patients with thrombosis had a GAPSS of 7.31±5.70, those without thrombosis – 4.00±4.81 (p=0.001). GAPPS values were higher in arterial thrombosis compared to venous thrombosis (10.40±25.30 versus 5.82±5.28; p=0.01). GAPSS levels ≥6 and ≥10 were analyzed to select GAPSS values at which a high risk of recurrent thrombosis and/or obstetric pathology could be indicated. All GAPSS levels had a significant association with clinical manifestations of APS. The quality of GAPSS by ROC analysis showed an area under the curve (AUC) for GAPSS of 0.697.Conclusion. GAPSS can be used to assess the risk of recurrence or development of thrombosis and/or obstetric pathology in patients with SLE in the Russian Federation. The GAPSS ≥6 values should be used to stratify patients with SLE into high risk group for recurrence of vascular complications. Further prospective follow-up is needed to confirm the value of GAPSS.